GLOBALIZATION: EMERGING TREND IN NIGERIAN CAPITAL MARKET OPERATION - Omah Ishmael; Fadayo Mathew Oluwalami; Adisa Abiodun James; Osamor I P (European Scientific Journal, ESJ, 2012)
Purpose: This paper aimed at examining the impact of globalization on Nigeria’s capital market operations. Included in the purpose are to examine the trend at which securities traded in the market has increased over the years with the advent of globalization. To investigate the impact of capital market growth in Nigeria and also to analyze the extent at which reform measures aimed at transforming the market in a global economy yielded result. Methodology/Approach: An empirical survey based on historical data and primary data procured from Lagos Stock Exchange, the Central Bank of Nigeria (CBN) and the Securities and Exchange Commission. Eighty (80) structured interview questionnaires were disseminated, of which forty (40) were administered at the Nigeria Stock Exchange (Lagos), Twenty-five (25) at securities and Exchange Commission (SEC) while the remaining fifteen (15) at the CBN. Findings: The capital market has been repositioned tentatively to achieve its objectives as an engine of growth and economic development. From its inception (1960) to the call-over action based period (globalization), sophistication in telecommunication network, electronic or Automated Trading System (ATS), On – line – Trading has contributed immensely to the global growth of the capital market world over. The electronic system which is the parental hydride of globalization. Has challenged and enhanced the operation of capital market in Nigeria, as transactions are carried out electronically and more efficiently, paving way for voluminous transactions per day. Research Limitations/Implications: Financial constraint has automatically re-defined the researchers’ need to expand the scope of coverage, limiting the investigation to Lagos metropolis. The establishment of “Cashless economy which is assumed to be the By-Product of globalization may create financial bottle – neck in a mono-cultural capitalist society, where technology is still at its infantry phase. Globalization, the parental hydride of cashless concept, may not be able to eliminate the influence of fraud managers in the key areas of the economy, including Nigerian capital market operation. Originality/Value: Globalization is a welcome idea in totality, its merits outweighed its limitations. It has influenced all aspects of human endeavour. This paper will energise further thinking in the area other than advantages of globalization.